Le rire dans la littérature populaire vietnamienne à l’époque féodale - Lo-Cicero, Minh Ha (2010)
I would like to focus on some aspects tied up with Laughter in Vietnamese popular literature in the feudal time, namely the Middle Age period and more specifically from the Xth to the XIVth centuries. The Vietnamese popular literature, of people’s creative endeavour and commonly of oral transmission from generation to generation, has largely contributed to characterize the Vietnamese culture and its national identity. Further back in time claimed Rabelais «Rire est le propre de l’homme». In the multi-millennial Vietnamese culture, laughter, embedded with an instructive/pedagogic significance while inculcating ethic values in its criticism of vicious and sinful conduct, has played an important role on people’s everyday life, simultaneously creating moments of joy, of entertainment, i.e. comic relief. Indeed, one laughs at misshapenness often linked to mistakes or the fake. The bad is the comic’s theme. One never laughs at beautiful and pleasant issues. Sometimes, bad is one’s inner feature without one’s own awareness. Thus, one tries to show one’s beauty. It is precisely in this paradoxical relation that bad becomes above all laughter’s origin. Laughter is also a weapon against negative phenomena greatly featuring the feudal society. In so doing, laughter has a deep social meaning. Vietnamese popular literature falls back to a great extent upon the comic, everyday laughter. For the Vietnamese commonly optimistic people, enjoying life, laughter is deeply and outstandingly imbued of a comic dimension. All along their history the Vietnamese have created a large number of bawdy stories aimed at satisfying their needs both for entertainment and struggle against negative influences, sins or even social inequalities and oppression. As a matter of fact, the Vietnamese popular literature comprises a valuable set of tales of comic nature, popular songs, as well as satiric poems, fables, buffoon’s tall tales (from popular theatre - Sân Khâu Chèo) making use of strategies to arouse laughter. Indeed, these are the underpinnings of the extremely rich satiric popular literature. 1 Actas do Colóquio Internacional «O Riso na Cultura Medieval» @ Universidade Aberta – Todos os direitos reservados 2 Actas do Colóquio Internacional «O Riso na Cultura Medieval» @ Universidade Aberta – Todos os direitos reservados Some Vietnamese popular tales, excerpts of buffoon’s roles in the popular theatre «Chèo» will be presented to describe the object of laughter and its triggering strategies. In the Vietnamese History, not only entailing the feudal period but also the contemporary one, laughter has always built on a satiric discursive component in the Vietnamese popular literature. Indeed, this literature constitutes a rich diversified treasure deeply inculcated in the Vietnamese culture, also shaping the borderlines of its national identity.